The COVID-19 pandemic and the gender gap in newly created domains of household labor - Abromaviciute, Jurgita; Carian, Emily K. (Sociological Perspectives, 2022)
In this study, we draw on interview data from 62 matched different-sex, dual-career spouses raising young children to examine the mechanisms behind the gender gap in household labor during the COVID-19 pandemic. We argue that the pandemic represents a unique case of social uncertainty and an opportunity to observe how structural conditions shape the gendered division of household labor. We find that under the rapid social transformation imposed by the pandemic, gender serves as an anchor and orienting frame for couples with young children. We argue that the pandemic (1) expanded traditional gender expectations to new domains of household labor and (2) heightened the importance of gendered explanations for the division of labor that justified intra-couple inequality. Our findings suggest that the particular structural conditions that characterize different times of uncertainty work through slightly different mechanisms, yet produce the same outcome: gender inequality, with long-lasting and wide-ranging implications. © The Author(s) 2022.
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; approches et analyses; care; charge mentale; conciliation famille-travail; discipline; division sexuelle du travail; famille; inégalités; projet charge mentale; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions; thématiques; travail; travail domestique; états-unis

“The workload is staggering”: Changing working conditions of stay-at-home mothers under COVID-19 lockdowns - Aslam, Awish; Adams, Tracey L. (Gender, Work and Organization, 2022)
The COVID-19 pandemic has drawn attention to the home as a work environment, but the focus has centered on the experiences of paid workers. Stay-at-home mothers (SAHMs), for whom the home was already a workplace, have received little attention. This article explores how pandemic-induced lockdowns impacted SAHMs' working conditions and their experiences of childrearing. Combining a Marxist-feminist conceptualization of domestic labor with a labor process framework, we performed a qualitative content analysis of vignettes SAHMs shared about their day-to-day domestic labor in an online mothering community. Our findings show that, under lockdown conditions, the primacy given to partners' paid work combined with children's increased demands for care and attention reduced SAHMs work autonomy and exacerbated gender inequalities in the home. Combining labor process theory with literature on motherwork illuminates the home as a gendered work environment and enhances understanding of how changing conditions of domestic labor can intensify gender inequalities (and workers' awareness of them) that typically remain “hidden in the household.”. © 2022 John Wiley & Sons Ltd.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; care; discipline; féminisme marxiste; féminisme matérialiste; inégalités; maternité; mères au foyer; projet charge mentale; périodes historiques; ressource en ligne; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; travail; travail de reproduction

L’émergence du concept de « violence obstétricale »: l’impact du mouvement féministe - Azcué, Mathieu; Tain, Laurence (Santé Publique, 2022)
La littérature scientifique a exploré de nombreux aspects relatifs à la notion de « violence », mais elle n’a jamais cherché à l’appréhender, à notre connaissance, en termes de généalogie vis-à-vis des mouvements féministes. Il s’avère par ailleurs que la formulation du concept de « violence obstétricale » est récente alors que l’expérience est ancienne. C’est ce paradoxe que cet article interroge. Plus précisément, cette contribution vise à élucider comment les mouvements féministes ont pu jouer un rôle facilitateur dans l’émergence de ce concept dont la généalogie s’ancre dans la réflexivité hospitalière et les mouvements féministes. En se saisissant de l’observation d’une association féministe engagée dans la pratique des accouchements alternatifs, cette étude vise à appréhender comment les dynamiques militantes ont ouvert la voie à ce nouveau concept. La recherche de terrain a permis d’identifier deux postures à partir d’entretiens mené auprès des usagères du système hospitalier. L’analyse de l’histoire de cette association montre que c’est un compromis interne à la rencontre entre ces deux postures qui a favorisé un espace de parole pour les parturientes et des négociations avec l’hôpital local pour des réalisations concrètes. La discussion analyse ces deux postures au prisme des points de vue féministes universaliste et différencialiste, ainsi que de la sociologie du corps. La conclusion interroge cette dynamique des mouvements sociaux, se demandant si on peut y observer un processus analogue.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; 2020-2029; approches et analyses; care; corps; cours; discipline; gynécologie; inégalités; médecine; obstétrique; patriarcat; pol4102; premier cycle; périodes historiques; santé; sciences; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; violences

L'expérience des proches aidantes dans un contexte d'urgence sanitaire : le travail de care durant la pandémie du COVID-19 - Bastien, Rose (Université du Québec à Montréal, 2022)
Le 13 mars 2020, le gouvernement du Québec annonce l’urgence sanitaire dans la province afin de contrer la pandémie du coronavirus. Une panoplie de mesures sanitaires est instaurée : le confinement de la population, la fermeture des commerces et services jugés non essentiels et l’implantation de gestes barrières. Les proches aidantes ont dû composer du jour au lendemain avec ces nouvelles restrictions. Leur travail de care est loin d’avoir cessé malgré la distance imposée et une perspective féministe sur les enjeux et conséquences des mesures sanitaires nous semble d’actualité. L’objectif de cette recherche est d’explorer l’expérience des proches aidantes confrontées aux mesures sanitaires de la COVID-19 déployées au Québec entre les mois de mars et mai 2020. Pour y arriver, nous avons réalisé une trentaine d’entrevues semi-dirigées auprès de dix proches aidantes s’occupant d’un.e proche adulte. Nous avons ensuite procédé à une analyse thématique afin de comprendre de quelle façon les mesures sanitaires ont interagi avec leurs tâches concrètes, ainsi que les aspects cognitifs et émotionnels de leur travail de care. Il en ressort que le travail des proches aidantes n’a pas été pris en compte lors de la gestion de la crise sanitaire, ce qui a exacerbé la lourdeur du travail réalisé. Les conséquences sont présentes pour les proches aidantes et pour leur proche. _____________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : Travail de care, travail cognitif, travail émotionnel, pandémie, COVID-19, dépendance, féminisme
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; care; discipline; pandémie; proche aidance; périodes historiques; québec; régions géographiques; santé; sciences humaines; sociologie; thématiques

Multidirectional carework across borders: Latina immigrant women negotiating motherhood and daughterhood - Bruhn, Sarah; Oliveira, Gabrielle (Journal of Marriage and Family, 2022)
Objective: The authors examine how transnational caregiving for immigrant women encompasses a set of complex gendered relationships and roles as mothers and daughters across national borders. Background: Scholars have explored transnational motherhood for women who migrate, often in search of employment, while their children remain in their nation of origin. Much of this research has focused on how migration transforms mother-child relationships. Intergenerational relationships between immigrant mothers and their own mothers, and the emotional and economic care that facilitates these ties, are often left out of the picture of transnational family life. Methods: Through ethnographic work, the authors conducted in-depth interviews with 63 mothers from Latin America who migrated to the greater Boston metropolitan area. Additionally, the authors draw from extensive participant observation with mothers at home, school, and sites throughout their communities. Results: The authors theorize how Latina immigrant women are at the center of a web of multidirectional carework as they negotiate intergenerational responsibilities as mothers and daughters. The women in the present study orient their decisions, paid labor, and child-rearing around sustaining transnational familial relationships across generations. As a result, they provide emotional and economic care in multiple directions, including maintaining relationships between children and grandchildren, even as they adapt to ruptures in receiving care from their own mothers. Conclusion: The authors argue that despite the gendered labor this emotional and economic work entails, the immigrant mothers in the present study value their carework, which ultimately becomes a means for them to exert agency in the face of anti-immigrant policies and discourses.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; amériques; care; femmes* immigrantes; projet charge mentale; périodes historiques; régions géographiques; soins aux enfants; thématiques; travail; travail émotionnel; états-unis

Women's overload during the pandemic: Unpaid care work, financial well-being, and stress - Bulog, Ivana; Pepur, Sandra; Smiljanić, Ana Rimac (Management : Journal of Contemporary Management Issues, 2022)
This study examines the relationship between unpaid care work, financial well-being, and stress levels among women during the COVID-19 pandemic. The pandemic caused downturns in the economies of countries worldwide and led to uncertainties and changes that created conditions for increased stress levels and consequently impaired well-being. In addition to social distancing and lockdown measures to cope with the virus, working from home, home schooling, caring for sick and older family members, and financial problems have added burdens and have proven to be additional personal and family stressors. The findings are based on an online survey conducted among women during the second lockdown in Croatia. Additional unpaid care work and lower financial well-being affect the increased stress felt by women during the pandemic. This is especially pronounced among women who are more involved in paid work. During the pandemic, additional unpaid care work, increased involvement in paid work, and jeopardized financial well-being were stressors for women. Our results indicate the importance of women s free time for their own and their families 'well-being.
Keywords: 2000 à aujourd'hui; 2020-2029; anxiété; care; conciliation famille-travail; covid-19; croatie; discipline; europe; famille; pandémie; projet charge mentale; périodes historiques; régions géographiques; santé; sciences de la gestion; thématiques; travail; travail gratuit; économie

Commoning care: Feminist degrowth visions for a socio-ecological transformation - Dengler, Corinna; Lang, Miriam (Feminist Economics, 2022)
This paper addresses the question of how to organize care in degrowth societies that call for social and ecological sustainability, as well as gender and environmental justice, without prioritizing one over the other. By building on degrowth scholarship, feminist economics, the commons, and decolonial feminisms, we rebut the strategy of shifting yet more unpaid care work to the monetized economy, thereby reinforcing the separation structure in economics. A feminist degrowth imaginary implies destabilizing prevalent dichotomies and overcoming the (inherent hierarchization in the) boundary between the monetized economy and the invisibilized economy of socio-ecological provisioning. The paper proposes an incremental, emancipatory decommodification and a commonization of care in a sphere beyond the public/private divide, namely the sphere of communitarian and transformative caring commons, as they persist at the margins of capitalism and are (re-)created by social movements around the world.HIGHLIGHTS Degrowth aims at creating human flourishing within planetary boundaries.As feminist degrowth scholarship, this study discusses degrowth visions for care work.It problematizes the shifting of yet more unpaid care work to the monetized economy.Instead, it proposes collective (re)organization in the sphere of the commons.Caring commons are no automatism for a gender-just redistribution of care work.
Keywords: approches et analyses; care; discipline; décroissance; environnement; féminisme décolonial; projet charge mentale; sciences de la gestion; thématiques; travail; travail du care; économie

Les travailleuses dans les organismes communautaires Famille au Québec : entre précarité et pauvreté? - Gauthier, Maude (Université du Québec à Montréal, 2022)
Cette recherche est une étude exploratoire sur les conditions de travail des femmes œuvrant dans les organismes communautaires Famille (OCF) au Québec. Basée sur neuf entrevues réalisées auprès de travailleuses de ce milieu, elle offre une analyse du sens que les femmes donnent à leur vécu et à leur expérience. Cette recherche a pour ambition de dresser un portrait des conditions de travail et des conditions de vie des femmes œuvrant dans ce milieu, en considérant la spécificité des OCF, ses rapports de pouvoir avec les bailleurs de fonds, ses dynamiques avec les acteurs sociaux et ses enjeux particuliers. À travers une lunette féministe matérialiste ancrée dans les théories du care, jumelées à une perspective critique du néolibéralisme, nous explicitons la façon dont les contraintes imposées au secteur communautaire Famille par l’État québécois et les bailleurs de fonds privés, affectent les conditions de travail et les conditions de vie des salariées évoluant dans ce milieu. Dans un premier temps, nous démontrons que les politiques néolibérales affaiblissent les OCF par la non-reconnaissance de leur spécificité, par leur sous-financement et par l’imposition de nombreux partenariats qui contribuent à limiter leur autonomie. Dans un deuxième temps, nous illustrons comment les politiques néolibérales, mais aussi le manque de reconnaissance et la dévalorisation de ce travail de care, précarisent les conditions de travail dans les OCF. Dans un troisième temps, nous explorons les situations de précarité et/ou de pauvreté découlant des conditions de travail. Au surplus, nous interrogeons le rapport potentiellement paradoxal qui peut émerger du fait d’intervenir auprès de familles qui ont des besoins socio-économiques similaires à ceux des travailleuses. _____________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : Organismes communautaires Famille, travailleuses, conditions de travail, féminisme matérialiste, care, néolibéralisme, précarité, pauvreté
https://uqam-bib.on.worldcat.org/oclc/1334508884
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; approches et analyses; biblioFem*; care; discipline; féminisme matérialiste; mémoires/thèses; néolibéralisme; périodes historiques; québec; ressource en ligne; régions géographiques; science politique; science politique et droit; thématiques; travail

Bijou de banlieue - Hébert, Sara (Éditions Marchand de feuilles, 2022)
« Dans cette autofiction, Sara Hébert puise dans l'imaginaire punk, le langage des meetings AA et les souvenirs du mariage de sa mère. De façon intime, touchante et combative, elle critique la positivité toxique, le mythe du prince charmant et la culture du travail sexiste. Elle espère, à travers ses tranches de vie, vous aider à reprendre confiance en vous, à repenser vos rapports aux patrons et à vous libérer des hommes-bouées. »– Résumé de l'éditeur.
Section: 349 pages : illustrations ; 23 cm
Keywords: 2000 à aujourd'hui; amériques; approches et analyses; arts; autofiction; canada; care; cours; discipline; har4600; maternité; premier cycle; périodes historiques; québec; rapports sociaux de sexe; régions géographiques; sofia; thématiques; travail; études littéraires

La recherche de reconnaissance des parents LGBTQ+ : une approche féministe illustrée - Lambert, Stéphanie (Université du Québec à Montréal, 2022)
Depuis une perspective située, cette investigation en travail social documente la négociation de modifications à apporter aux représentations culturelles des familles LGBTQ+ circulant dans l’espace public québécois, par quatre parents LGBTQ+ et l’étudiante-chercheure. L’exercice, sous forme de focus group, avait pour but de favoriser l’échange et de créer de nouvelles images pouvant leur sembler plus justes en fonction de leurs propres expériences de parentalité. La démarche visait également à répondre à la question suivante : quelle forme de reconnaissance est recherchée par les parents LGBTQ+ montréalais, et de quelle manière? Elle s’inscrit dans les théories de la justice, où la reconnaissance est un élément clé à la pleine participation des individus et des collectivités dans leur société. Une analyse du contenu thématique, émergeant des réflexions des participants-es au focus group, recense trois statuts subordonnés (selon Nancy Fraser) auxquels les parents LGBTQ+ font face. Il s’agit de statuts liés au projet national québécois, au sexisme et au genrisme, et à la famille naturelle. De plus, l’attention portée aux interactions des parents permet d’observer le souci à autrui prenant place au sein de leurs échanges, à la lumière des quatre phases du care de Tronto et des perspectives de Ricoeur sur la reconnaissance. La quête de reconnaissance est donc exposée non seulement comme une lutte personnelle, mais aussi telle une démarche démontrant l’attention à soi et à l’autre. Cette observation va à l’encontre de certaines représentations culturelles rencontrées où les parents LGBTQ+ sembleraient davantage préoccupés par leurs propres désirs, besoins et droits, que ceux de leur entourage, incluant leurs enfants et leurs pairs marginalisés. Cette recherche qualitative à caractère exploratoire a recours à l’illustration pour interpeller le public ciblé, éliciter les données, développer l’analyse, présenter les matériaux et uniformiser le travail. Les limites observées sont liées au petit échantillonnage comme au caractère artificiel (initié par l’étudiante) du processus de recherche de reconnaissance en groupe. Des recherches ultérieures auprès d’enfants et d’adolescents de parents LGBTQ+, ou encore auprès d’autres groupes minoritaires pourraient mettre en corrélation et solidifier les données mises de l’avant. _____________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : reconnaissance, parentalité, homoparentalité, transparentalité, pluriparentalité, LGBTQ+, queer, care, justice, Fraser, Tronto, Ricoeur, féminisme, bande dessinée, illustration, représentations culturelles, famille, travail social.
https://uqam-bib.on.worldcat.org/oclc/1368201405
Keywords: 2000 à aujourd'hui; 2020-2029; LGBTQIA2+; amériques; approches et analyses; bande-dessinée; biblioFem*; care; discipline; identités LGBTQIA2+; justice sociale; maternité; montréal; mémoires/thèses; parentalité; périodes historiques; queer; québec; représentations; ressource en ligne; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; travail social; étude qualitative

Indigenous parents and child welfare: Mistrust, epistemic injustice, and training - Leckey, Robert; Schmieder-Gropen, Raphael; Nnebe, Chukwubuikem; Clouthier, Miriam (Social & Legal Studies, 2022)
The settler state's taking of Indigenous children into care disrupts their communities and continues destructive, assimilationist policies. This article presents the perceptions of lawyers, social workers and judges of how Indigenous parents experience child welfare in Quebec. Our participants characterized those experiences negatively. Barriers of language and culture as well as mistrust impede meaningful participation. Parents experience epistemic injustice, wronged in their capacity as knowers. Mistrust also hampers efforts to include Indigenous workers in the system. Emphasizing state workers’ ignorance of Indigenous family practices and the harms of settler colonialism, participants called for greater training. But critical literature on professional education signals the limits of such training to change institutions. Our findings reinforce the jurisdictional calls away from improving the system towards empowering Indigenous peoples to run services of child welfare. The patterns detected and theoretical resources used are relevant to researchers of other institutions that interact with vulnerable populations.
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; approches et analyses; australie; canada; care; cours; cycles supérieurs; discipline; droit; enfants autochtones; fem9000; injustice; inégalités; nouvelle-zélande; océanie; politique assimilationniste; périodes historiques; racisme; régions géographiques; santé; science politique et droit; sciences humaines; sciences sociales; système colonial; systèmes d'oppressions; thématiques; violences; états coloniaux

Dysphoria mundi: le son du monde qui s'écroule - Preciado, Paul B. (Bernard Grasset, 2022)
«Dysphoria mundi est un texte mutant, qui hybride essai, philosophie, opéra, poésie et autofiction, afin de rendre compte de la transition planétaire en cours. Ce livre apprend au regard à distinguer ce que la propagande nihiliste mainstream cherche à dissimuler : les déplacements irréversibles qui s'opèrent dans les sphères sociales, politiques, sexuelles. Il n'est pas question d'un passé mythique ni d'un avenir messianique, mais d'un présent révolutionnaire. Le XIXe siècle était hystérique ; le XXe, schizophrène ; notre époque est dysphorique. Anxiété généralisée, troubles post-traumatiques, syndrome de dépendance, dysphorie de genre, destruction légitimée de l'écosystème... Voici l'hypothèse que propose ce livre : généraliser la notion de dysphorie afin de la comprendre non pas comme une maladie mentale, mais comme une dissidence politique. L'auteur organise une archive implacable de la fabrication/destruction nécropolitique de la subjectivité dans la modernité, et dessine une cartographie des pratiques d'émancipation susceptibles de transformer l'avenir. On dit souvent qu'il nous est devenu plus facile d'imaginer la fin du monde que de penser la fin du capitalisme. Preciado persiste à observer les preuves de pratiques alternatives à cette impasse : de nouveaux modes de vie jusqu'alors disqualifiés comme improductifs et anormaux se présentent désormais comme la seule issue.»–Page 4 de la couverture.
Keywords: 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; 2020-2029; LGBTQIA2+; approches et analyses; arts; care; corps; cours; discipline; disphorie; har4600; identités LGBTQIA2+; philosophie; premier cycle; périodes historiques; queer; santé; sciences humaines; sexualité; thématiques; transféminisme; études littéraires

Don’t give mum chocolates for Mother’s Day. Take on more housework, share the mental load and advocate for equality instead - Ruppanner, Léa (The Conversation, 2022)
Keywords: 2000 à aujourd'hui; approches et analyses; care; charge mentale; charge émotionnelle; discipline; hétérosexisme; patriarcat; projet charge mentale; périodes historiques; ressource en ligne; sciences humaines; sociologie; systèmes d'oppressions; thématiques; travail; travail invisible

Better stories for a gender equal and fairer social recovery from outbreaks: learnings from the RESISTIRÉ project - Strid, Sofia; Schrodi, Colette; Cibin, Roberto (Gender & Development, 2022)
La pandémie a radicalement modifié l’organisation de la société, avec une augmentation du travail à domicile, de l’enseignement à domicile et de la présence en ligne, le tout avec des implications spécifiques (non)intentionnelles sur le travail de soins rémunéré et non rémunéré. Ces implications, comme celles d’autres crises, sont sexistes et se manifestent selon le sexe, l’âge, le handicap, l’origine ethnique/la race, le statut migratoire, la religion, la classe sociale et les intersections entre ces inégalités. Si de nombreuses études ont identifié ces impacts inégaux et négatifs et soulignent d’importantes inégalités liées aux soins, la contribution spécifique de cet article est différente, à savoir celle de mettre en évidence des pratiques inspirantes comme de meilleures histoires de et dans le domaine des soins pendant la pandémie. L’objectif est de rendre ces meilleures histoires visibles et de les considérer comme des moyens d’atténuer les impacts inégaux de la COVID-19 et de ses réponses politiques. Théoriquement, l’approche est basée sur les « meilleures histoires », telles que développées par Dina Georgis (2013, Better Story. Queer Affects from the Middle East , New York : State University). L'article utilise des données quantitatives et qualitatives, recueillies auprès des 27 États membres de l'UE, de l'Islande, de la Serbie, de la Turquie et du Royaume-Uni, dans le cadre du projet européen H2020 RESISTIRÉ.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; care; covid-19; europe; intersectionnalité; pandémie; projet charge mentale; périodes historiques; régions géographiques; santé; thématiques; travail; travail du care